Modeling of Plasma Affected Thermal Profile in Solids During Laser Materials Processing - Hussain, Mohammed A.; Saleem, Jewamir M.; Alwan, Adil A. (Iraqi Journal of Laser, 2003)
A new scheme of plasma-mediated thermal coupling has been implemented which yields the temporal distributions of the thermal flux which reaches the metal surface, from which the spatial and temporal temperature profiles can be calculated. The model has shown that the temperature of evaporating surface is determined by the balance between the absorbed power and the rate of energy loss due to evaporation. When the laser power intensity range is 107 to108 W/cm2 the temperature of vapor could increase beyond the critical temperature of plasma ignition, i.e. plasma will be ignited above the metal surface. The plasma density has been analyzed at different values of vapor temperature and pressure using Boltzmann’s code for calculation of electron distribution function. This analysis has been used to determine the temporal distribution of the net heat flux, which reaches the solid surface. The net heat flux has been proved to vanish at high plasma density. Accordingly the temporal and spatial distributions of temperature profiles within the solid metal have been modeled depending upon the net heat flux which reaches the target surface.